The historic achievement of the Iraqi national football team in the 2007 Asian Football Championship (a historical study) (College of Basic Education Research Journal, 2025)
Research consists of five chapters. First chapter deals with  introduction of  research, its importance,  problem,  objectives, and  human, temporal, and spatial areas of research. The second  deals with  matches of  Iraqi national team in the 18th Arabian Gulf Championship in  Emirates. As for  third chapter, it includes  matches of  Iraqi national team in  fourth West Asian Championship in Jordan. The fourth one includes  matches of  Iraqi national team in  2007 Asian Nations Championship, while  fifth chapter deals with a set of conclusions and recommendations.